Panoramic Viewfinder: Providing a Real-time Preview to Help Users Avoid Flaws in Panoramic Pictures - Baudisch, Patrick; Tan, Desney; Steedly, Drew; Rudolph, Eric; Uyttendaele, Matt; Pal, Chris; Szeliski, Rick (OZCHI 2005 Conference for the Computer-Human Interaction Special Interest Group of the Human Factors Society of Australia, 2005)
Image stitching allows users to combine multiple regular-sized photographs into a single wide-angle picture, often referred to as a panoramic picture. To create such a panoramic picture, users traditionally first take all the photographs, then upload them to a PC and stitch. During stitching, however, users often discover that the produced panorama contains artifacts or is incomplete. Fixing these flaws requires retaking individual images, which is often difficult by this time. In this paper, we present Panoramic Viewfinder, an interactive system for panorama construction that offers a real-time preview of the panorama while shooting. As the user swipes the camera across the scene, each photo is immediately added to the preview. By making ghosting and stitching failures apparent, the system allows users to immediately retake necessary images. The system also provides a preview of the cropped panorama. When this preview includes all desired scene elements, users know that the panorama will be complete. Unlike earlier work in the field of real-time stitching, this paper focuses on the user interface aspects of real-time stitching. We describe our prototype, individual shooting modes, and an implementation overview.